Pengaruh Bentuk Latihan Variasi (Rondo) Terhadap Kemampuan Passing Futsal Pada Ekstrakulikuler SMP Mentari Indonesia - Ramadon, Aprizal Rizki; Prawira, Asrori Yudha; 'Ala, Faridatul; Ningrum, Desy Tya Maya; Candra, Juli (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The rondo variation training method is one of the most effective training approaches for improving passing skills in futsal. This training facilitates teamwork in implementing game strategies, thereby maximizing the chances of winning. This study aims to first determine the improvement of the varied training model (rondo) on futsal passing skills in the futsal extracurricular activities at SMP Mentari Indonesia. Second, to determine the level of passing skills of students in the futsal extracurricular activity at SMP Mentari Indonesia before being given the rondo training method. The method used was a quantitative method with an experimental design, specifically a pre-experimental design in the form of a One Group Pretest–Posttest Design. The results of this study indicate that the rondo training method has a significant impact on improving basic passing skills among participants in the futsal extracurricular activity at SMP Mentari Indonesia.